Purple in a Black & White World: Self-Determination Theory and Transgender Military Service - David A. Levy; James E. Parco; Sarah R. Spears (Journal of Basic & Applied Sciences, 2015)
We offer a theoretical framework to advance our understanding of the psychology of transgender service members—the most understudied and mysterious class of US military personnel. Using grounded theory methods with interview data collected from clandestinely-serving active-duty, guard and reserve military members from the US Army, Navy, Air Force and Marine Corps who self-identified as transgender or transsexual, we reveal a latent structure of Self Determination Theory (Deci & Ryan, 1985; Deci & Ryan, 2000; Ryan & Deci, 2000). The variance in our data heavily centers around the concepts of autonomy, competence and relatedness, illustrating how post-DADT military personnel policy, which excludes open transgender service, impacts the mental well-being of transgender service members.